Coexistence of genetically modified seed production and organic farming in Chile COMMENT - Sánchez, M.; Campos, Hugo (Informa UK Limited, 2021)
The seed industry in Chile has thrived since the implementation of a stringent, voluntarily self-imposed coexistence strategy between genetically modified organisms (GMOs) and non-GMO seed activities. GMO varieties of maize, soybean, and canola represent the vast majority of biotech seeds produced in Chile. Chile's exports of genetically modified (GM) seeds and organically grown food products (which excludes GM seeds and materials) continue to expand. Organic Chilean farmers predominantly produce and export fruits such as blueberries, wine grapes, and apples. Under normal agricultural conditions, the inadvertent presence of GMOs in non-GMO or organic crops cannot be ruled out. Producers of organic foods are required to implement stringent measures to minimize contact with any non-organic crop, regardless of whether these crops are GM. Only very small amounts of organic maize, soybean, and canola - if any - have been produced in Chile in recent years. Given the characteristics and nature of Chile's agriculture, the direct impact of the GM seed industry on organic farming in Chile is likely to be negligible. The Chilean experience with coexistence between GM seed and organic industries may inform other countries interested in providing its farmers with alternative agricultural production systems.